Improving bean production and marketing in Africa (IBPMA) April 2020 - March 2021 Report - Pan-Africa Bean Research Alliance (2021)
The IBPMA project is being implemented across 31 PABRA member countries with the goal of: “Reducing poverty among smallholder farmers, especially women, in sub-Saharan Africa by reducing food insecurity, increasing incomes and strengthening climate-smart agriculture”. The project has facilitated the deployment of the Commodity Corridor principles across 31 bean growing countries, with emphasis given to 23 countries that make up nine corridors: East Africa Red Mottled (EAREM), Yellow Bean (YEBECO), Red Bean, White Pea Bean, Large White, Tanzania, Zambia, Malawi Corridor (TAZAMA), TOGHABU, SEMAGUI and CAMCOCA.